Pengaruh Berbagai Konsentrasi Pulp Buah Naga Merah pada Pembuatan Set Yoghurt terhadap Total Bakteri Asam Laktat, Nilai pH, dan Total Asam - Altasya Frilanda; Wendry Setiyadi Putranto; Jajang Gumilar (Unpad Press, 2022)
Set yogurt is a yogurt product that has a characteristic thick texture containing dry ingredients about 20% derived from fresh milk and skims milk. The addition of Red Dragon Fruit Pulp to yogurt is used as a good substrate with simple sugar components to stimulate the growth of lactic acid bacteria, pH value, and total acid set yogurt. The method used in this study is a Completely Randomized Design (CRD) in various concentrations of each treatment were 0% (P0), 5% (P1), 10% (P2), 15% (P3), and five replications. The obtained data were statistically analyzed by ANOVA at = 5% and if there were significant differences, further tests will be carried out using the Duncan Multiple Region Tests (DMRT). The results showed significant differences (p<0,05) in various concentrations of Red Dragon Fruit Pulp on total acid bacteria, pH value, and total acid. The red dragon fruit pulp concentration of 15% added to the milk resulted in the best set yoghurt with a total lactic acid bacteria of 9,52 x 108 CFU/ml, pH value of 4,19, and total acidity of 1,12%.